The Role of Progressive Philosophy in the Curriculum Based on John Dewey's Theory - Musyarapah Musyarapah (Al-Hayat Al-Istiqomah Foundation, 2017)
Programmatism is a diverse stream containing activities that lead to thorough thinking skills training, so that learners can think systematically, through scientific means such as providing a variety of empirical data and theoretical information, providing analysis, consideration and making conclusions to solve the problems at hand. One of the figures that greatly influenced progresivism was John Dewey. In practice, Dewey recommends learning by doing learning methods and problem solving as a more perfect learning tool by providing a theoretical and experimental based framework. This is in line with one of the goals of the education curriculum in Indonesia.